Linear optimization technique applied in the Processing-Marketing Outlet (PMO) of the Philippine Carabao Center at Central Mindanao University (PCC AT CMU), Musuan, Bukidnon, Philippines - Bagares, Paolo Augustus Ramos (CMU Graduate Journal, 2017)
The study was conducted to determine a production plan that maximized profits at the Processing-Marketing Outlet (PMO) of PCC at CMU, Musuan, Bukidnon, Philippines. Specifically, it aimed to (1) identify products to be incorporated as decision variables in the objective function; (2) Calculate the net profits per unit of identified products to be incorporated as objective function coefficient; (3) formulate constraints as mathematical equalities or inequalities in the linear program; and (4) identify problems that impede operations at the PMO. The data needed were obtained via interview, while the calculations were performed using simple accounting procedures - Microsoft Excel's propriety Solver was used to solve the quarterly Linear Programs constructed for 2017. Though PCC at CMU produced various products, only six were considered in the formulation of the objective function as these were considered to be flagship products, or products that the agency was well-known for; these were: chocomilk (500ml and 1L variants), fresh milk (500ml and 1L variants), pastillas de leche, and white cheese. Individual net profits of each product showed that white cheese was the most profitable at P32.94, despite being the least sellable, followed by chocomilk 500ml at P27.10, pastillas de leche P24.81, chocomilk 1L P19.53, freshmilk 500ml and freshmilk 1L at P14.42 and P11.89 respectively. In addition to the baseline constraints on demand, raw materials availability and labor time requirements, the constraints formulated also included targets on raw milk to be processed, target peso-sales, and target improvement in ROI. Initial results showed that no optimum solution could be found for the constructed linear program as the constraints on raw milk to be processed and on demand could not be satisfied simultaneously and the former was violated at every solution provided by MS Excel Solver. This led to the reformulation of the linear program which excluded the constraint on raw milk to be processed to allow for profit-maximizing output with the results showing that, in order to achieve optimum profits of P2,782,981.72, the PMO needed to produce the following for 2017: 59,913 units of chocomilk 500ml, 28,666 units of chocomilk 1L, 40,122 units of fresh milk 500ml, 15,099 units of freshmilk 1L, 878 units pastilles de leche, and 1,705 units of white cheese. The general problem that beset the PMO is one that is peculiar amongst some, if not all, government enterprise agencies, that is, the lack of competitive drive. The subsidized nature of these institutional enterprise models have a tendency to dull the competitiveness that ought to be displayed by any business entity.